Predictors of Steal in Hemodialysis Access. Issue 10 (October 2017) - Korn, Abraham; Alipour, Hamid; Zane, Joshua; Gray, Kelsey; Ryan, Timothy; Kaji, Amy; De Virgilio, Christian; Bowens, Nina
Pathological steal is an uncommon but devastating complication after the creation of arteriovenous access for hemodialysis. In this study, we sought to assess predictors of clinically significant steal syndrome and to further evaluate the outcome of differing surgical treatment approaches. A retrospective analysis was performed of 282 consecutive patients undergoing hemodialysis access at a single center from November 2014 to April 2016. Adequate follow-up to assess for the development of steal was obtained in 237 patients. One hundred and fifty-seven (66%) patients were male, 152 (64%) Hispanic, and 164 (69%) had diabetes. Forty-three (18%) had prior access procedures. Autologous fistula was created in 218 patients (92%). Pathologic steal occurred in 15 patients (6.7%). On univariate analysis, significant predictors of steal included female sex [P = 0.03, odds ratio (OR) = 3.3, CI [1.1–9]), no systemic heparin at operation (P = 0.02, OR = 5.0, CI [1.4–10]), use of angiotensin-converting enzyme inhibitor (P = 0.003, OR = 5.6, CI [1.7–18.6]), and increased vein size (3.1 vs 4.1 mm P = 0.01). Twelve patients had steal managed with an intervention, but only one patient received distal revascularization. Furthermore, we identify key predictors of clinically significant steal syndrome while demonstrating that distal revascularization and/or fistula ligation are rarely indicated treatment modalities.